Competitive intelligence and improving patronage of the twenty first century academic libraries in Nigeria (2022)
The paper discussed the employment of competitive intelligence for improving patronage of the 21st century academic libraries. It explored literature on; the concept of competitive intelligence, characteristics of the twenty first century academic library, attributes of competitive advantage in academic libraries and competitive intelligence activities in Nigerian academic libraries. It was discovered that funds and the necessary skill-sets were required for an academic library to develop to the point of having a competitive edge over other libraries. Also literature revealed that only few libraries especially private university libraries were already treading the path of gaining the competitive advantage for attracting increased patronage. The paper concluded that having competitive advantage is a function of better application of knowledge gained through competitive intelligence as a major factor for staying relevant and be able to attract the 21st century academic sophisticated library clientele. Also adequate provision of funds for innovation and upscale facilities and services is key to attracting patrons. Therefore, it was recommended that library and information science professionals should seek ways of generating funds apart from library subventions and be knowledgeable about their users, they should be sensitive to their environment as well as brace up to the changes taking place in their internal and external environments by acquiring relevant skill-sets and deploy both traditional, non-traditional (ICT) and creative/innovative methods to meet the highly specialized information needs of users thereby attracting more patrons while they strive to acquire some facilities that beautify and make the environment inviting and conducive.